PERSEPSI ORANG TUA SISWA TERHADAP PEMBELAJARAN BILINGUAL PADA PENDIDIKAN ANAK USIA DINI - DJUHARIE, OTONG SETIAWAN (JURNAL PENDIDIKAN BAHASA DAN SASTRA, 2011)
A number of early child education programs in Bandung apply bilingual instruction, Indonesian and English. This mini research aims at investigating the opinions of the childrenâs parents on their childrensâs following this bilingual program at Early Child Education of Mutiara Bunda Kindergarten Bandung. This research applies descritipve quantitative approach in which parents are surveyed through questionnaires. The findings show that parents find their childrenâs ability in English is good and they perceive that bilingual instruction in early child education enables the children to be well-informed and alert in cultural difference as well as makes the children communicative, independent, creative, broad-minded, and more ready for globalization era.Keywords: bilingual program, early child education, language education